The Effect of Servant Leadership and Remuneration on Doctor Job Satisfaction Mediated by Work Motivation at UPT RSUD RAA Soewondo Pati - Mujianto; Kertati Sumekar; Sutono (PT FORMOSA CENDEKIA GLOBAL, 2023)
This study aims to analyze the influence of servant leadership on the work motivation of doctors. This research was conducted at UPT RSUD RAA Soewondo Pati with a total population of 66 respondents and a sample of 40 respondents using the proportional random sampling technique. Data collection techniques using a questionnaire instrument The data analysis technique uses PLS (partial least squares). The results of this study indicate that servant leadership has a significant effect on the work motivation of doctors. Remuneration has a significant effect on the work motivation of doctors. Servant leadership has a significant effect on doctors' job satisfaction. Remuneration has a significant effect on a doctor's job satisfaction. Work motivation has a significant effect on a doctor's job satisfaction. Servant leadership and remuneration had a significant effect on a doctor's job satisfaction, which was mediated by work motivation.